Mykola Chvyl'ovyj. Eine Studie zu Leben und Werk - Kratochvil, Alexander (Slavistische Beitraege, 1999)
In the present study the first chapter deals with the biography of Chvyl'ovyj's open and controversially discussed questions. Against this background, a biographical sketch of its own arises through the critical comparison of previously published biographical material. The following chapter on Chvyl'ovyj's journalism will be preceded by an outline of literary politics in Ukraine in the 1920s. This section, which is supplemented with corresponding passages in the biography, presents in a cross-section the representatives and programs of the Ukrainian literary associations and the course of the literary discussion, with emphasis on Chvyl'ovyj's activities. This background is crucial for the understanding of Chvyl'ovyj's journalism, which is also examined in the third chapter from the perspective of Spengler reception.